Screening for frailty among older patients with cancer that qualify for abdominal surgery. Issue 1 (January 2015) - Kenig, Jakub; Zychiewicz, Beata; Olszewska, Urszula; Richter, Piotr
Abstract Objective The Geriatric Assessment (GA) is an established method for evaluating and optimizing diagnostic and treatment plans. However, it requires experience and is time-consuming. Therefore, a variety of screening methods have been developed. The aim of this study was to compare their accuracy for predicting frailty among older patients with cancer qualified for abdominal surgery based on comparison to the GA. Material and Methods One hundred and thirty five consecutive patients ≥ 65 years of age were prospectively enrolled. The diagnostic performance of eight screening tests was evaluated: The Vulnerable Elderly Survey (VES-13), Triage Risk Screening Tool (TRST), Geriatric 8 (G8), Groningen Frailty Index (GFI), abbreviated Comprehensive Geriatric Assessment (aCGA), Rockwood, Balducci and Fried score. Results The prevalence of frailty as diagnosed by the GA was 73%. Screening methods identified frail patients in 40–75.5% of cases. The sensitivity and specificity of these tests in predicting frailty were 52%–97% (Fried score-G8) and 44–100% (G8-Rockwood score), respectively. The positive and negative predictive values were 82–100% (Balducci–Rockwood) and 43–84% (TRST–G8), respectively. Age significantly influenced the predictive value of the screening tests whereas gender and type of cancer did not. Conclusion At present, there is no universal screening test that adequately identifies frailty in at risk older patients. The results of this study showed that the aCGA and G8 were the best screens for older patients with cancer that qualified for elective abdominal surgery; the G8 had the highest sensitivity and negative predictive value and the aCGA was a good overall assessment tool.